Discovery of N-[(4R)-6-(4-Chlorophenyl)-7-(2,4-dichlorophenyl)-2,2-dimethyl-3,4-dihydro-2H-pyrano[2,3-b]pyridin-4-yl]-5-methyl-1H-pyrazole-3-carboxamide (MK-5596) as a Novel Cannabinoid-1 Receptor (CB1R) Inverse Agonist for the Treatment of Obesity - Yan, Lin; Huo, Pei; Debenham, John S; Madsen-Duggan, Christina B; Lao, Julie; Chen, Richard Z; Xiao, Jing Chen; Shen, Chun-Pyn; Stribling, D. Sloan; Shearman, Lauren P; Strack, Alison M; Tsou, Nancy; et al. (Journal of medicinal chemistry, 2010)
This paper describes the discovery of N-[(4R)-6-(4-chlorophenyl)-7-(2,4-dichlorophenyl)-2,2-dimethyl-3,4-dihydro-2H-pyrano[2,3-b]pyridin-4-yl]-5-methyl-1H-pyrazole-3-carboxamide (MK-5596, 12c) as a novel cannabinoid-1 receptor (CB1R) inverse agonist for the treatment of obesity. Structure−activity relationship (SAR) studies of lead compound 3, which had off-target hERG (human ether-a-go-go related gene) inhibition activity, led to the identification of several compounds that not only had attenuated hERG inhibition activity but also were subject to glucuronidation in vitro providing the potential for multiple metabolic clearance pathways. Among them, pyrazole 12c was found to be a highly selective CB1R inverse agonist that reduced body weight and food intake in a DIO (diet-induced obese) rat model through a CB1R-mediated mechanism. Although 12c was a substrate of P-glycoprotein (P-gp) transporter, its high in vivo efficacy in rodents, good pharmacokinetic properties in preclinical species, good safety margins, and its potential for a balanced metabolism profile in man allowed for the further evaluation of this compound in the clinic.